Analysing the effect of dietary prebiotics and probiotics on gut bacterial richness and diversity of Asian snakehead fingerlings using T‐RFLP method - Mohammad Bodrul, Munir; Marsh, Terence L; Blaud, Aimeric; Roshada, Hashim; Wizilla Janti, Joshua; Siti Azizah, Binti Mohd Nor (John Wiley & Sons Ltd, 2018)
This study was designed to evaluate the effects of three prebiotics (β‐glucan, galacto‐oligosaccharide [GOS], mannan‐oligosaccharide [MOS]) and two probiotics (Saccharomyces cerevisiae, Lactobacillus acidophilus) on the microbiome of snakehead during growth of fingerlings. In addition, the experiment evaluated the capacity of Channa striata fingerlings to retain the benefits derived from these supplements after withdrawal. Throughout the study, it was observed that supplementation with dietary prebiotics and probiotics led to significant (p < 0.05) change in gut bacterial profile and improvement in gut morphology. Terminal restriction fragment length polymorphism (T‐RFLP) was used for the comparative analysis of gut communities and all 46 of the T‐RFLP detected phylotypes were present in the Lactobacillus supplemented fish, while significantly fewer were detected in controls and other experimental supplement regimes. Histological studies and electron microscopy revealed that both the prebiotic and probiotic treated fish had significantly longer and wider villi and deeper crypts compared to the controls. The microvilli length, as evaluated with electron microscopy, was also longer in all treated fish compared to controls. Furthermore, this study is the first to report the absence of differences in sustaining the efficacies attained after intake of β‐glucan, GOS, MOS and live yeast upon post feeding with an un supplemented feed, over a prolonged period.